2017
DOI: 10.1159/000454944
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Benefit of Overall Survival between Patients with Non-Small-Cell Lung Cancer Harboring <b><i>EGFR</i></b> Exon 19 Deletion and Exon 21 L858R Substitution

Abstract: Background: Exon 19 deletion (Del19) and exon 21 L858R substitution (L858R), which account for 90% of epidermal growth factor receptor (EGFR) mutations as common mutations, are associated with favorable outcomes with EGFR-tyrosine kinase inhibitors (TKIs) compared with other uncommon EGFR mutations in non-small-cell lung cancer (NSCLC). However, whether there are differences in overall survival (OS) between patients with these common EGFR mutations remains controversial. Methods: The subjects studied were 74 N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Although our small sample size may have reduced the statistical power of the OS comparison, this is nevertheless in concordance with findings from Peking University Cancer Hospital [19] . In contrast, EGFR-TKIs provided a significant OS benefit to patients harboring 19 del compared with L858R mutations as reported in another study [20] . In our study, the OS of patients with L858R mutations was longer than that of patients with EGFR 19 del (26.5 months).…”
Section: Discussionmentioning
confidence: 63%
“…Although our small sample size may have reduced the statistical power of the OS comparison, this is nevertheless in concordance with findings from Peking University Cancer Hospital [19] . In contrast, EGFR-TKIs provided a significant OS benefit to patients harboring 19 del compared with L858R mutations as reported in another study [20] . In our study, the OS of patients with L858R mutations was longer than that of patients with EGFR 19 del (26.5 months).…”
Section: Discussionmentioning
confidence: 63%
“…Del19 and L858R mutations in EGFR have different predictive and prognostic impacts. [ 34 , 35 ] In a combined analysis of the Lux-lung 3 and 6 trials investigating afatinib versus chemotherapy, overall survival was improved in patients with the Del19 mutation but not in patients with the L858R mutation. [ 26 ] However, utilizing the del19 mutation to guide treatment decisions has not yet gained solid supporting evidence.…”
Section: Discussionmentioning
confidence: 99%
“…36 It has been reported that NSCLC patients harboring EGFR 19del and 21L858R mutations present diverse biological profiles, clinical features and prognoses, 37 and previous studies have demonstrated various responses to first-generation EGFR-TKIs between NSCLC patients harboring EGFR 19del and 21L858R mutations. [38][39][40][41][42][43][44] Results from a meta-analysis of 22 eligible trials involving 1082 patients showed that advanced NSCLC patients harboring EGFR 19del mutations had longer OS and PFS than those with 21L858R mutations, 45 which may be explained partly by the higher proportion of the EGFR T790M mutation in patients with EGFR 19del mutations. 46 However, the exact mechanisms responsible for the difference in the responses to EGFR-TKIs between advanced NSCLC patients with EGFR 19del and 21L858R mutations remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%